SYNTHESIS OF A POLYMERIZED IONIC LIQUID MEMBRANE (PILM) WITH BRILLIANT YELLOW FOR ITS USE AS A pH INDICATOR - Yipmantín Ojeda, Andrea G. (2015)
A polymerized ionic liquid membrane (PILM) has been synthesized by copolymerization of 3-butyl-1-vinylimidazolium bromide with acrylonitrile and then loaded with brilliant yellow dye (AB) describing an anion exchange process. The main objetive of this synthesis is the measurement of pH in aqueous solutions between pH 6,5 and 8,0; close to neutral conditions. Both PILM and PILM-AB membranes were characterized by FT-IR spectroscopy and their pH-response was measured by UV-Vis spectrophotometry.